2016
DOI: 10.1517/17425255.2016.1164691
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamics and pharmacokinetics of sodium zirconium cyclosilicate [ZS-9] in the treatment of hyperkalemia

Abstract: ZS-9 has a unique mechanism of action consisting of thermodynamically favorable sequestration of potassium ions, enabling rapid trapping and removal of excess potassium. The potassium lowering action of ZS-9 is predictable and rapid, leading to significant reduction of serum potassium within 1 hour of administration by irreversibly eliminating excess potassium rather than acting via intracellular translocation. Its safety profile, including gastrointestinal events, has been generally similar to that of placebo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…The similar reduction in sK + observed with SZC at 1 hour suggests that at 1 hour the potassium‐lowering effect of the background insulin and glucose treatment is dominant. The greater reduction in sK + observed with SZC compared with placebo at 2 hours may reflect the rapid biological effect of SZC, which has been shown consistently in clinical trials to lower sK + as early as 1 hour after administration 22‐24 . Unfortunately, a substantial proportion of patients were missing central laboratory potassium measurements at 4 hours, which reduced the ability to detect treatment differences at this time point.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The similar reduction in sK + observed with SZC at 1 hour suggests that at 1 hour the potassium‐lowering effect of the background insulin and glucose treatment is dominant. The greater reduction in sK + observed with SZC compared with placebo at 2 hours may reflect the rapid biological effect of SZC, which has been shown consistently in clinical trials to lower sK + as early as 1 hour after administration 22‐24 . Unfortunately, a substantial proportion of patients were missing central laboratory potassium measurements at 4 hours, which reduced the ability to detect treatment differences at this time point.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies have demonstrated the capacity of SZC to bind potassium in localized environmental conditions mimicking the entire GI tract, including acidic conditions of the duodenum 19,22 . Nonselective exchange resins, such as SPS, function in the colon where potassium concentration is highest; by contrast, SZC is highly selective for potassium and may bind as early as the upper GI tract where high amounts of potassium are present 19,22 . This likely explains the rapid effect of SZC in lowering sK + within 1 hour, which has been observed consistently in clinical trials 22‐24 .…”
mentioning
confidence: 99%
“…IOH-NPs are a saline composition with [ZrO] 2+ as an inorganic cation and one or more functional organic anions resulting in the general composition [ZrO] 2+ [ R function OPO 3 ] 2- . The [ZrO] 2+ cation, which guarantees the insolubility of the IOH-NPs in water, is highly biocompatible and clinically approved 25,26. The organic anion [ R function OPO 3 ] 2- has certain functionalities such as fluorescence or pharmaceutical activity.…”
Section: Methodsmentioning
confidence: 99%
“…78 Similar to SPS, patiromer nonspecifically binds K þ ions in the colon where K þ concentrations are the highest, 79 whereas SZC exhibits non-pH-dependent binding of K þ with high specificity throughout the gastrointestinal tract, including the small intestine (duodenum and jejunum). 80 In randomized, placebo-controlled studies of patients with hyperkalemia, serum K þ concentrations were significantly reduced over 4 weeks with twice-daily patiromer [81][82][83] and were maintained within the normal range for a further 8 weeks 83 or for up to 52 weeks 81 with ongoing treatment. In randomized studies of SZC in patients with hyperkalemia, serum K þ concentrations were significantly reduced within 48 hours with 3-times-daily administration of SZC, [84][85][86][87] and normokalemia was effectively maintained for 12 to 28 days with once-daily SZC.…”
Section: Nondialysis Options For Managing Hyperkalemiamentioning
confidence: 99%